CONSTRUING HOW PEOPLE INTERACT WITH LANGUAGE - Liliek Soepriatmadji (Universitas Stikubank (UNISBANK) Semarang, 2011)
There are three strands of meanings believed to be communicated in every single utterance uttered by a speaker Hallidays (1994). This article, therefore, tries to explain how a speaker’s inner or outer world of experience, one of the three strands of meaning, is interpersonally negotiated. The metalanguage used to construe an interaction with language will be explained in detail. A sample analysis is also provided to accompany the construal of how interpersonal interaction with language occurs. Key words: metafunctions, interpersonal meaning, interaction with language, role in exchange.